Propositional Logic: Formulas, Models, Tableaux - Ben-Ari, Mordechai (Mathematical Logic for Computer Science, 2012)
Propositional logic is a simple logical system that is the basis for all others. Propositions are claims like ‘one plus one equals two’ and ‘one plus two equals two’ that cannot be further decomposed and that can be assigned a truth value of true or false. From these atomic propositions, we will build complex formulas using Boolean operators: ‘one plus one equals two’ and ‘Earth is farther from the sun than Venus’.